Mental health and relationships of comradeship in political parties of the radical left - Barbosa, Clara (Argumentum, 2023)
This article addresses research conducted with 19 militants from Minas Gerais, and three political parties from the Brazilian radical left; the Brazilian Communist Party – PCB; the Liberty and Socialism Party – PSOL; and the Socialist Unified Workers’ Party – PSTU. It considers how these organisations have developed analyses and political actions related to mental health, both intra and extra-party. Along with interviews, we conducted a bibliographic review of output from the Marxist field dealing with mental health and militancy. The results emphasise that the collectivisation of expressions of suffering and the strengthening of humanising and emancipatory political bonds (relationships between comrades) in these spaces help to alleviate the suffering of individuals, as the common understanding is that the problem has a social root.